Perceived Ease of Use’s Effects on Behavioral Intention Mediated by Perceived Usefulness and Trust - Widiar, Greta; Yuniarinto, Agung; Yulianti, Ida (International Journal Labs, 2023)
Background: It is important for the banking industry to know the Behavioral Intentions of consumers in adopting technology so that they are willing to adopt mobile banking as a medium for transactions in their daily banking activities. Aim: This study intends to explain and analyze the effect of Perceived Ease of Use on Behavioral Intention either directly or indirectly through the mediation of Perceived Usefulness and Trust in mobile banking users. Method: This type of research was explanatory research with a quantitative approach that collects data by distributing questionnaires to 230 respondents. Data analysis using Structural Equation Modeling Partial Least Squares (SEM-PLS). The population in this study was mobile banking users in Indonesia who have never used mobile banking, have used mobile banking 1-2 times and more than 2 times in the last 6 months. Findings: The results of this study suggest that mobile banking providers improve Perceived Ease of Use integrated with Perceived Usefulness and Trust of the provided application in order to establish sustainable or long-term relationships.